ANALISIS PERSEPSI PENGUNJUNG TERHADAP ATRIBUT EKONOMI PADA WISATA HUTAN MADAPI TNKS - Oktoyoki, Hefri; Wahyuni, Heliza; Kurniati, Yasih (LPPM UNIVERSITAS BINA INSAN, 2021)
This study was to determine the visitor's perception of the economic attributes of the TNKS Madapi Forest tourism in Rejang Lebong Regency. This research was conducted in February-March 2020, the research location was determined purposively. Respondents in this study were visitors who were doing camping, outbound activities, research, environmental education, and forest exploration (tracking) in the TNKS Madapi Forest. The method of determining respondents is done by survey or observation methods. The data collection methods are primary data and secondary data, while the data analysis method uses Spearman Rank Correlation data analysis. Based on the results and discussion, it is known that the average visitor is satisfied with the tourism attributes that have been provided by the management of the TNKS Madapi Forest. The attraction or attribute that most visitors like is the view of the trees in the TNKS Madapi Forest. Based on the analysis, it is known that there is no influence between tourism attributes and the number of visitors in the TNKS Madapi Forest.